UJI DIAGNOSTIK NT pro NATRIURETIC PEPTIDE (NTpro BNP) GAGAL JANTUNG KONGESTIF - Dewi Indah Noviana Pratiwi; Suwarso Suwarso; Osman Sianipar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Congestive Heart Failure (CHF) is a syndrome associated with disturbances of heart structure and function, as a result of various cardiovascular diseases. These disturbances decrease ventricle ability to pump or fill blood in physiological pressure, which causes limitation on the ability to excercise or daily activities without dyspnea and fatigue.Early diagnosis is important to initiate prompt treatment that can prevent further disease development. To measure heart hormone in this case, NT pro Natriuretic Peptide (NT pro BNP) can be use as a more ideal examination for early detection of CHF. The aim of this study is to investigate the clinical performance of NT pro BNP and assess the cut-off point 125 pg/mL compared to clinic (Framingham criteria) and or echocardiogram in the diagnosis CHF.The diagnostic test was carried out using clinical (Framingham criteria) and or echocardiography as reference methods. The subject of this research was patients with cardiac and blood vessel disorders complaints at risk of developing congestive heart failure, who came to the Emergency Department at Dr. Sardjito Hospital Yogyakarta, supported by clinical data, radiology, other laboratory test, electrocardiography and echocardiography. The diagnosis of CHF was obtained by conducting investigation toward echocardiography examination reading in patient’s medical record. Receiver Operating Characteristics (ROC) curve analysis was conducted using SPSS 13.0 program. Sensitivity, specificity, positive and negative predictive value, accuracy and likelihood ratios were measured with 2x2 table by CAT marker program. Forty-six of fifty-seven specimens were from congestive heart failure (CHF). At 125 pg/mL as a cut-off point, regardless the interval between the onset of the symptoms and taking of blood samples, the sensitivity, specificity, positive and negative predictive value and diagnostic accuracy are 96%, 36%, 86%, 67%, 84% respectively. Likelihood ratios for positive and negative results are 1.50 and 0.12. NT pro BNP measuring is expected to give more benefit than the conventional signal, so that an early diagnosis can be achieved accurately in a timely manner.